Evaluation and Selection of Poultry Using Probit Method - S. Sushkov, V.; A Babushkin, V.; N. Lobanov, K.; V. Grihina, N. (International Journal of Engineering and Technology, 2018)
The purpose of the research is comparative evaluation of fertilizing ability of cocks-breeders in absolute rates (arithmetic mean) and relative (probit), held at egg-laying hens of â€œKuchinskyâ€ PBP. Fertilization of eggs, hatchability of eggs and poultry rearing were taken into account during evaluation. Evaluation of cocks in terms of incubation qualities showed that eggs fertilization was 81.4%, hatchability of eggs â€“ 76.6% poultry rearing â€“ 62.4%. On average one cock fertilized 194.8 eggs, from which 149.3 poults were reared. Biometric processing of incubation qualities identified that influence of cocks was reliable (r > 0.999) on all three indicators, and hatching quality were interconnected, the coefficient of multiple correlation was on the level of 0.939 (p > 0.999). Comparative evaluation and selection of cocks in absolute terms and with the help of probit-method confirmed high coincidence of their ranks. Rank correlation coefficients between evaluations of these 2 methods of eggs fertilization, hatching and poults rearing was at the level of 0.999â€“1.000.Â Â